Kerjasama pertahanan Indonesia – Jerman dalam pengadaan senjata - Yusuf Thaahir; Zabdan Fatih (Journal of Current Research In Multidisciplinary, 2023)
The population of Surakarta City in 2020 is 522,364 people. Of these, the male population is lower than the female population. The male population is 257,043 people, while the female population is 291,935 people. While the sex ratio in Surakarta is 0.969, this shows that the male population is smaller than the female population. Judging from the development trend of the population in 2016 to 2020 there is an increase every year with a growth rate of 0.44% in 2020.